About business valuation - book value vs. market value - Monte, Ana Paula (2019)
This paper aims to develop a method that allows the evaluation of companies, according to the respective sector of activity, in a simple and fast way, comparing the value obtained through the application of the Market Value Added method with multiple Price to Sales. To obtain a fair value that reflects the expected returns based on forecast there are several methods. Each method follows its own assumptions and methodologies, with the purpose of finding the value of the company. One of widely used methods is the Market Value Added method, or MVA method, that belongs to the group of methods based on cash flows. This method consists of the current value of all future Economic Value Added (EVA). EVA is the difference between the value of the company and the total capital invested. Another method widely used is the method of multiples, which is part of the group of methods based on patrimonial approach. Each multiple has a numerator and a denominator, where the numerator can be the book value or the market value, such as the market price. On the other hand, the denominator may be a measure of equity, such as the book value of equity, or an enterprise value measure, such as operating or sales revenues. In the present paper is intended to create the multiple of price to sales for the companies of the sector of activity CAE 01 - Agriculture, animal production, hunting and related service activities, using the results obtained by the method MVA, as market price, taking into account the last 5 years of activity of the sector. Based on the obtained value, the multiple PS is determined for the activity sector. In this way, the value of a company, with this economic activity, can be determined by the multiplication of its sales by the multiple PS.